Investigating the Rheology and Strength of Self-compacting Geopolymer Concrete Using Blast Furnace Slag and Flyash - Mehta, Geeta; Sharma, Sanjay Kumar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Building energy requirements have risen drastically in the modern era, partly because of expanding populations and broadened human lifestyles. Greater energy demand, depletion of fossil resources, and environmental concerns constitute crucial motivating factors in building enticing and sustainable infrastructure. In the current situation, environmental management is an urgent problem that has to be highlighted.
Keywords: blast furnace slag; alkaline solution; geo-polymerization; flyash; self-compacting geopolymer concrete